A Study of Legal Geography Approach: Inheritance Distribution of Tionghoa Ethnic Community in South Kalimantan - Firqah Annajiyah Mansyuroh (Faculty of Law, Universitas Pekalongan, 2021)
The development of legal research demonstrates the importance of an interdisciplinary approach in studying legal issues. In addition, legal issues also need to be studied more critically and not to see them as a product of a vacuum without the influence of non-legal factors. This paper describes the legal subjugation of the Tionghoa Ethnic Community of South Kalimantan in inheritance law which is divided into three areas, that are urban, rural, and coastal. The interdisciplinary approach with various critical theories has been developed in the study of spatial law with a critical legal geographical framework. However, the study of spatial law in Indonesia has not developed much of the discourse in studying legal issues. This paper has shown that the approach of legal geography in legal studies shows the difference in the inheritance law of Tionghoa community in South Kalimantan domiciled in urban, rural, and coastal. The law that lives in society is not only a matter of juridical and planology, but also there are social, cultural, and economic interests that attract each other to influence each other. Legal Geography; Inheritance,Distribution; Tionghoa Kalimantan